Liprotein (a) in transplant recipients: a case controlled prospective clinical study - Sharaf El Din, U A A; Mansour, M; El Hamamsy, M; El Henawy, O; El Khodary, M; Abdel Ghany, S; Barsoum, R S (African Journal of Nephrology, 2016)
This work was designed to assess the impact of renal transplantation (TX) on the lipid profile of chronic renal failure patients (CRF). It included thirty normal controls (N) and one hundred CRF cases treated by TX divided into three groups: Group I: ten CRF patients were seen during preoperative assessment and followed at one and six months after TX. Group II: thirty TX patients were followed postoperatively for one year. Group III: sixty recipients were examined just once after successful TX. The following parameters were estimated and followed according to the plan of each group: serum level of Lp (a), total cholesterol (TC), triglycerides (TG), HDL, LDL, total proteins (TP), albumin (Alb) and creatinine. Duplex study of the carotid arteries was done and followed up for one year in a group of ten patients randomly selected from group II. Serum Lp (a) showed significant decrease after TX which continued during the twelve months of follow up, this level was still significantly higher at any time compared to N (P<0.0001 in all). Beside the favorable effect of TX on Lp (a) it had a variable effect on oth er lipid parameters assessed pre and postoperatively. Whereas a decrease in TG was observed (p<0.001) an increase occurred in TC (p<0.001), HDL (p<0.005) and LDL (p<0.001). There was no significant correlation between Lp (a) on one hand and either age, sex, creatinine, TP, Alb or other lipid parameters analyzed in various studied groups. None of the ten patients who had duplex study showed carotid atherosclerotic changes over one year of follow-up. Conclusion: TX resulted in favorable effects on the serum concentrations of the recently reported independent atherogenic risk factor. Lp (a). The absence of carotid atherosclerotic changes in the present study does not rule out the widely acceptanced atherogenic activities of Lp (a ). This could be partly due to the significant increase in HDL cholesterol after TX.